30(48x+12)=16x+-60

Simple and best practice solution for 30(48x+12)=16x+-60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 30(48x+12)=16x+-60 equation:


Simplifying
30(48x + 12) = 16x + -60

Reorder the terms:
30(12 + 48x) = 16x + -60
(12 * 30 + 48x * 30) = 16x + -60
(360 + 1440x) = 16x + -60

Reorder the terms:
360 + 1440x = -60 + 16x

Solving
360 + 1440x = -60 + 16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16x' to each side of the equation.
360 + 1440x + -16x = -60 + 16x + -16x

Combine like terms: 1440x + -16x = 1424x
360 + 1424x = -60 + 16x + -16x

Combine like terms: 16x + -16x = 0
360 + 1424x = -60 + 0
360 + 1424x = -60

Add '-360' to each side of the equation.
360 + -360 + 1424x = -60 + -360

Combine like terms: 360 + -360 = 0
0 + 1424x = -60 + -360
1424x = -60 + -360

Combine like terms: -60 + -360 = -420
1424x = -420

Divide each side by '1424'.
x = -0.2949438202

Simplifying
x = -0.2949438202

See similar equations:

| s^2+3s=0 | | 7x+12=9x-6 | | x^2+20=-9 | | 8x-4=6x+14 | | 6x-2=4x+4 | | -12x+9+24x+4=43 | | 0=-3y^2+7y+6 | | x-1=8x-8 | | 3(-2x+4)+5(4x-3)=4(-5x-2) | | 9x-3=4x-1 | | 7x-5=4x+7 | | =0.1428571429m+-0.4285714286y | | -(5y+5)-(-4y-7)=-1 | | 4(3x-7)-5(4x-2)= | | 7x+7=9x-9 | | 23x+67=55x-40 | | x^2+4x+6=10 | | 54*4= | | x+57,x=3 | | 4.39(5)+3.42N=76.11 | | 8x+2=7(x-4)+8 | | 6-5y=7-6y | | 2x+4=-7(-7x+6) | | 8y+2=7y-4 | | .6u-7=9-.6u | | 5-5x+8+2x+4x-2=6+4*3 | | 1.12a=149000000 | | 7g+5=12g-25 | | 6p-(5p-5)=-8-2(p+12) | | 3x^4(7x^3-4x-1)= | | .25+9=10-.75r | | 5x(1-x)=5(x-2) |

Equations solver categories